Functional analyses of small secreted cysteine‐rich proteins identified candidate effectors in Verticillium dahliae. (10th March 2020) - Wang, Dan; Tian, Li; Zhang, Dan‐Dan; Song, Jian; Song, Shuang‐Shuang; Yin, Chun‐Mei; Zhou, Lei; Liu, Yan; Wang, Bao‐Li; Kong, Zhi‐Qiang; Klosterman, Steven J.; Li, Jun‐Jiao; et al.
Abstract: Secreted small cysteine‐rich proteins (SCPs) play a critical role in modulating host immunity in plant–pathogen interactions. Bioinformatic analyses showed that the fungal pathogen Verticillium dahliae encodes more than 100 VdSCPs, but their roles in host–pathogen interactions have not been fully characterized. Transient expression of 123 VdSCP‐encoding genes in Nicotiana benthamiana identified three candidate genes involved in host–pathogen interactions. The expression of these three proteins, VdSCP27, VdSCP113, and VdSCP126, in N. benthamiana resulted in cell death accompanied by a reactive oxygen species burst, callose deposition, and induction of defence genes. The three VdSCPs mainly localized to the periphery of the cell. BAK1 and SOBIR1 (associated with receptor‐like protein) were required for the immunity triggered by these three VdSCPs in N. benthamiana . Site‐directed mutagenesis showed that cysteine residues that form disulphide bonds are essential for the functioning of VdSCP126, but not VdSCP27 and VdSCP113. VdSCP27, VdSCP113, and VdSCP126 individually are not essential for V. dahliae infection of N. benthamiana and Gossypium hirsutum, although there was a significant reduction of virulence on N. benthamiana and G. hirsutum when inoculated with the VdSCP27 / VdSCP126 double deletion strain. These results illustrate that the SCPs play a critical role in the V. dahliae– plant interaction via an intrinsic virulence function and suppress immunity following infection. Abstract : Small cysteine‐rich proteins secreted by Verticillium dahliae play critical roles in interactions with hosts via an intrinsic virulence function and can suppress immunity following infection.